2008
DOI: 10.1590/s1413-35552008000200005
|View full text |Cite
|
Sign up to set email alerts
|

Benefícios da cinesioterapia respiratória no pós-operatório de colecistectomia laparoscópica

Abstract: Introduction: Pulmonary function changes following abdominal surgery lead to reduced pulmonary volume, thus compromising gas exchanges. Objective: To evaluate the effects of respiratory kinesiotherapy on pulmonary function and respiratory muscle strength in patients who underwent laparoscopic cholecystectomy. Methods: Twenty women and 16 men (age 48.4 ± 9.55 years) who underwent laparoscopic cholecystectomy were prospectively studied. They were randomly divided as follows: 17 subjects performed breathing exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
13

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 25 publications
(36 reference statements)
1
23
0
13
Order By: Relevance
“…Gastaldi et al 23 observed a reduction in respiratory muscle strength on the first postoperative day after laparoscopic cholecystectomy similar to the findings of other studies. However, PImax (p<0.05) and PEmax (p<0.05) showed an early return to normal levels by the third or fourth postoperative day.…”
Section: ■ Discussionsupporting
confidence: 80%
“…Gastaldi et al 23 observed a reduction in respiratory muscle strength on the first postoperative day after laparoscopic cholecystectomy similar to the findings of other studies. However, PImax (p<0.05) and PEmax (p<0.05) showed an early return to normal levels by the third or fourth postoperative day.…”
Section: ■ Discussionsupporting
confidence: 80%
“…Of the six included studies, one had a final PEDro score of 1, one had a final score of 3, two had a final score of 5, one had a final score of 6, and one had a final score of 7 ( Table 2). The overall quality of the included studies was low, with the exception of the studies by Forgiarini et al 25 (score 7) and Gastaldi et al 24 (score 6; Table 2). Among the included studies, the one by Hallböök et al 20 divided the participants into three intervention groups: mobilization, thoracic physical therapy, and thoracic physical therapy plus bronchodilator.…”
Section: Resultsmentioning
confidence: 94%
“…Based on the abstracts, 22 articles were eligible for a full review, and a total of six articles [20][21][22][23][24][25] that fulfilled all of the inclusion criteria were selected ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations